ANALISIS FENOMENA SPRING-BACK/SPRING-GO FACTOR PADA LEMBARAN BAJA KARBON RENDAH MENGGUNAKAN PENDEKATAN EKSPERIMENTAL - Khoirudin Khoirudin; Sukarman Sukarman; Nana Rahdiana; Ahmad Fauzi (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
Bending angle accuracy is the primary output variable that should achieve in the V-bending process. The spring-back/spring-go factor is one of the essential variables that affect the accuracy of the bending angle. This study uses the Taguchi experimental method using four input parameters and multiple practical levels. The input parameters used in this research are V-die opening, punch angle (punch angel), punch speed (punch speed) and bending force. The V-die opening used two experimental levels at the practical level, while the other three parameters used three functional groups. This work selected SPCC-SD low carbon steel material with a material thickness of 0.8 mm in this study. The results of the ANOVA analysis showed that the punch angle is the main factor that affects the spring-back/spring-go factor, with the highest contribution of 76.15%. This condition is also following the results of the S/N ratio analysis, where the punch angle parameter has a delta of 0.125, followed by the punch speed, V-die opening, and bending force. These parameters have a delta value of 0.026, 0.022, and 0.009, respectively.